2021
DOI: 10.1007/s10666-020-09743-5
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Methane Emission in OECD Countries for 1750–2014: a Fractional Integration Approach

Abstract: The statistical structure of the methane emissions in a group of 36 OECD countries has been examined in this work for the time period 1750-2014 using techniques based on fractional integration. This allows us to determine the degree of persistence of the series and the potential presence of trends in the data. Our results indicate that all series are highly persistent, with orders of integration above 1 in the majority of the cases. Linear (positive) trends are observed in approximately half of the cases. One … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…4 Methane is a chemically reactive gas which, when oxidating, brings a rise in carbon emissions and stratospheric water vapor, thereby distorting the amount of other compounds such as tropospheric ozone and hydroxyl (Wuebbles and Tamaresis 1993 ; Solarin et al 2022b ). As pointed out by Solarin and Gil-Alana ( 2021 ), despite not directly harming crop yields or human health, the ozone generated with the oxidation of methane is responsible for respiratory morbidity and premature mortality.…”
Section: Introductionmentioning
confidence: 99%
“…4 Methane is a chemically reactive gas which, when oxidating, brings a rise in carbon emissions and stratospheric water vapor, thereby distorting the amount of other compounds such as tropospheric ozone and hydroxyl (Wuebbles and Tamaresis 1993 ; Solarin et al 2022b ). As pointed out by Solarin and Gil-Alana ( 2021 ), despite not directly harming crop yields or human health, the ozone generated with the oxidation of methane is responsible for respiratory morbidity and premature mortality.…”
Section: Introductionmentioning
confidence: 99%
“…This rapid increase of CH 4 has primarily been caused by the imbalance of CH 4 sources and sinks, with a significant amount of CH 4 emitted by human activities [5]. However, the spatiotemporal variations of CH 4 emissions have not been well understood [6]. For instance, China is a major CH 4 emitter but has not yet compiled its own CH 4 emission inventory [7].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies confirmed that the atmospheric concentration of CH 4 reached an unprecedented level since records began, exhibiting an accelerating upward trend [5]. However, unlike CO 2 emissions, methane emissions have not been well understood in both developed and developing countries [6][7][8]. For example, China, to date, has not yet compiled its own CH 4 emission inventory.…”
Section: Introductionmentioning
confidence: 99%